General practitioners in Styria – who is willing to take part in research projects and why?: A survey by the Institute of General Practice and Health Services Research - Poggenburg, Stephanie; Reinisch, Manuel; Höfler, Reinhild; Stigler, Florian; Avian, Alexander; Siebenhofer, Andrea (Wiener Klinische Wochenschrift, 2017)
Summary Increasing recognition of general practice is reflected in the growing number of university institutes devoted to the subject and Health Services Research (HSR) is flourishing as a result. In May 2015 the Institute of General Practice and Evidence-based Health Services Research, Medical University of Graz, initiated a survey of Styrian GPs. The aim of the survey was to determine the willingness to take part in HSR projects, to collect sociodemographic data from GPs who were interested and to identify factors affecting participation in research projects. Of the 1015 GPs who received the questionnaire, 142 (14%) responded and 135 (13%) were included in the analysis. Overall 106 (10%) GPs indicated their willingness to take part in research projects. Factors inhibiting participation were lack of time, administrative workload, and lack of assistance. Overall, 10% of Styrian GPs were willing to participate in research projects. Knowledge about the circumstances under which family doctors are prepared to participate in HSR projects will help in the planning of future projects.